2019
DOI: 10.1007/s10068-019-00619-3
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origin discrimination of pepper (Capsicum annuum L.) based on multi-elemental concentrations combined with chemometrics

Abstract: The concentrations of twenty-four elements in twenty-five peppers from three cultivated regions in Guizhou Province (China) were analyzed. The chemometric data processing, including one-way analysis of variance, principal component analysis, linear discriminant analysis (LDA), and orthogonal partial least squares discriminant analysis (OPLS-DA) were executed to differentiate the peppers. Consequently, the contents of 16 elements (Arsenic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 29 publications
11
23
2
Order By: Relevance
“…Earlier studies showed that authentication rates for geographical origin using the S‐LDA model were 92.1, 92.0, and 94.1% for olive oils, pepper, and sea cucumber, respectively, indicating satisfactory identification. The S‐LDA model was therefore also used to trace the geographical origin of tea leaves from the three locations in this study (Pu'an, Duyun, and Liping) in Guizhou, based on the 16 correlated mineral elements mentioned above.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier studies showed that authentication rates for geographical origin using the S‐LDA model were 92.1, 92.0, and 94.1% for olive oils, pepper, and sea cucumber, respectively, indicating satisfactory identification. The S‐LDA model was therefore also used to trace the geographical origin of tea leaves from the three locations in this study (Pu'an, Duyun, and Liping) in Guizhou, based on the 16 correlated mineral elements mentioned above.…”
Section: Resultsmentioning
confidence: 96%
“…These studies proved the suitability of mineral elements as potential fingerprinting markers for the authentication of the geographical origin of tea. However, this research was conducted to trace the geographical origins of agro‐products only taking into account differences in element contents in agro‐products with different origins . The role that mineral elements in soils played in identifying the geographical origins of agro‐products was not clearly known or understood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this result was of significance considering that various metabolite components even with minor contents could be used as individual indicators in the 1 H NMR analysis. By comparing the analysis results of the mineral elements [ 25 ] and sensor characteristics [ 24 ] of red peppers from other regions in China using various multivariate statistical analysis methods, it can be observed that their regional scopes were different. However, it can be confirmed that the second-derivative FT-IR method can be sufficiently utilized to discriminate the origins of red pepper powders.…”
Section: Resultsmentioning
confidence: 99%
“…The geographical classification of Asian red peppers has also been studied [ 23 , 24 , 25 , 26 ]. Yin et al proposed a simple method to determine the geographical origins of red peppers from various regions in China through multivariate analysis of sensory characteristics, such as color, taste, and smell [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation